Factors that promote or predict infidelity - CHOY, Bryan Kwok Cheng (Institutional Knowledge at Singapore Management University, 2021)
Depending on the theoretical perspective taken (e.g., biological, evolutionary, relationships science, individual differences), different factors can promote or predict infidelity. While each factor may independently contribute to infidelity, it is likely that the occurrence of infidelity is contingent on a multitude of factors.